The AKT antagonist AZD5363 suppresses features associated with cancer progression in human larynx cancer cells - Şanlı, Fatma; Barlak, Neslişah; Kılınç, Ahsen; Çapık, Özel; Aytatlı, Abdülmelik; Karatas, Omer Faruk (The European Research Journal, 2020)
Objectives: Larynx cancer (LCa) represents approximately 30% of all cancers seen in the head and neck region, with an unchanged overall survival rate over the last decades. Although several novel diagnostic and therapeutic options has been developed, an effective treatment strategy is not currently available due to the high metastatic and recurrent potential of LCa. In this study, we aimed at investigating the inhibitory potential of AZD5363 on the phenotypes associated with LCa progression in vitro.Methods: The impacts of AZD5363 on the proliferation, colony formation, and apoptosis potentials of HEp-2 cells were tested using Cell Viability Detection Kit-8, soft agar assay and Annexin V-FITC Apoptosis assay, respectively. Migration features of cells were evaluated using scratch and transwell migration assays.Results: We showed that AZD5363 increased phosphorylation of AKT and inhibited the phosphorylation of its downstream effector GSK3β in an in vitro LCa model in line with the findings of previous studies carried out with different cancer types. Besides, AZD5363 successfully suppressed proliferative, clonogenic, and migratory features of HEp-2 cells through induction of apoptosis.Conclusions: We revealed putative functions of AZD5363 in vitro that points its potential to be used as an adjuvant agent against LCa. However, further comprehensive molecular and clinical research is needed to elucidate the potential use of AZD5363 in LCa therapy in detail.